2019
DOI: 10.1213/ane.0000000000004291
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Costs of Low-Value Preoperative Testing for Carpal Tunnel Release Surgery

Abstract: Background: The American Society of Anesthesiologists’ (ASA) Choosing Wisely Top-5 list of activities to avoid includes: “Don’t obtain baseline laboratory studies in patients without significant systemic disease (ASA I or II) undergoing low-risk surgery - specifically complete blood count, basic or comprehensive metabolic panel, coagulation studies when blood loss (or fluid shifts) is/are expected to be minimal.” Accordingly, we define low value preoperative tests (LVTs) as those performed prior to minor surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Based on this evidence and consistent with our previous work, 11 we define low-value preoperative tests (LVTs) as screening tests ordered prior to low-risk procedures in generally healthy patients. This definition is in accordance with recommendations from the American Board of Internal Medicine Choosing Wisely Campaign list of low-value perioperative practices, 3 the American College of Cardiology/American Heart Association guidelines on perioperative cardiovascular evaluation for noncardiac surgery, 12 the US Agency for Healthcare Research and Quality, 13 and the United Kingdom’s National Institute for Health and Care Excellence for preoperative screening tests for patients undergoing low-risk surgery.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Based on this evidence and consistent with our previous work, 11 we define low-value preoperative tests (LVTs) as screening tests ordered prior to low-risk procedures in generally healthy patients. This definition is in accordance with recommendations from the American Board of Internal Medicine Choosing Wisely Campaign list of low-value perioperative practices, 3 the American College of Cardiology/American Heart Association guidelines on perioperative cardiovascular evaluation for noncardiac surgery, 12 the US Agency for Healthcare Research and Quality, 13 and the United Kingdom’s National Institute for Health and Care Excellence for preoperative screening tests for patients undergoing low-risk surgery.…”
Section: Introductionsupporting
confidence: 54%
“…Previous studies in different contexts have also found high rates of preoperative screening tests before low-risk surgery, as well as patient factors, such as age and comorbidities, that were associated with receiving preoperative tests. 21-24 Our recent study of preoperative tests prior to CTR in the US Veterans Administration 11 found that 47.0% of CTRs in patients with American Society of Anesthesiologists Physical Status Classification I or II were preceded by at least 1 LVT, with substantial variability between facilities (range, 0%-100%; interquartile range, 36.3%). Older age, female sex, and nonlocal anesthesia were associated with higher odds of receiving at least 1 LVT.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Harris et al and Taylor et al investigated preoperative testing prior to carpal tunnel release and thyroid and/or parathyroid procedures in similar patient cohorts from 2015-2017 and 2015-2018, respectively. 17 , 18 Harris et al found that 47.0% of the carpal tunnel release patients received PLT, 18 and Taylor et al found that 58.7% of the thyroid and/or parathyroid surgery patients received PLT. 17 These results in combination with our own are encouraging and suggest that the guidelines have been incorporated somewhat into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…First, while we developed rigorous methods to establish that tests were preoperative and had been validated previously, it is uncertain whether all tests were ordered as a result of the planned surgery. 12 Second, to avoid including just subpopulations where testing may have been justified, we selected all patients who underwent cataract surgical procedures within 1 fiscal year and conducted a broad, epidemiologic, population-level study and adjusted for a diverse set of predictive factors including detailed comorbidities. Third, VHA is a capitated, publicly funded health care system, so patterns and drivers of preoperative test ordering behavior may be different than other contexts, including non-VHA health care systems.…”
Section: Discussionmentioning
confidence: 99%
“…We used methods developed for a prior study in carpal tunnel surgery patients within the VHA to identify preoperative LVTs using CPT codes. 12 A test was considered preoperative if it occurred within 30 days prior to cataract surgery and if it occurred within 30 days after an encounter in a specific VHA clinic where preoperative screening tests are typically ordered, including those that are explicitly dedicated to preoperative care (eg, VHA clinic “stop” code 416–Pre-Surgery Evaluation by Non-MD; 419–Anesthesia Pre-Op/Post-Op Consult; 432–Pre-Surgery Evaluation by MD; 433–Pre-Surgery Evaluation by Nursing) or are likely related to preoperative care (ie, VHA clinic “stop” code 407–Ophthalmology). We excluded tests occurring within 30 days of noncataract procedures (eg, coronary artery bypass graft) that might have justified testing.…”
Section: Methodsmentioning
confidence: 99%